Main report of th Public Service Review Commission - Nigeria (Lagos : Federal Ministry of Information, Print. Division, 1974)
The Report is presented in two parts: (i) The Main Report and (ii) The Grading and Pay Report, which is in four volumes. The Main Report is structured to present both the findings that pertain to particular parts of the public services, in Chapter 5 to 14, as well as those that apply broadly across all public services, in Chapters 1 to 4 and 15 to 18.
Cover title.
rpm 12/03/2018
Loans
Keywords: Civil service; Civil service-Nigeria